PENINGKATAN DURABILITAS DAN KEKUATAN TANAH CLAYSHALE MENGGUNAKAN METODE STABILISASI SECARA KIMIAWI - Khansa Nuansa Oktofani; Syahril; Indra Noer Hamdhan (Jurnal Teknik Sipil, 2026)
This study examines the improvement of clayshale soil characteristics using a combination of Bledug Kuwu mud and emulsified asphalt. Clayshale is classified as problematic soil due to its expansive nature, low shear strength, and susceptibility to weathering and slaking. Stabilization aims to enhance soil stability, making it more suitable for construction. Unlike previous studies, this research investigates the synergistic effect of Bledug Kuwu mud, a natural waste material, with emulsified asphalt for soil stabilization to improve shear strength and unconfined compressive strength (UCS). The methodology involves collecting clayshale samples from Banten, which were subsequently stabilized in the laboratory using Bledug Kuwu mud at varying percentages (6%, 10%, 14%, and 18%) and 8% emulsified asphalt. Testing was conducted after curing periods of 0, 3, 7, and 14 days. The results indicate an increase in qu (unconfined compressive strength) from 0.410 kg/cm² to 1.919 kg/cm² and cu (undarained shear strength) from 0.201 kg/cm² to 0.960 kg/cm². The combination of Bledug Kuwu mud and emulsified asphalt enhances the soil matrix structure, reduces its expansive behavior, and improves resistance to moisture variation. This method has the potential to serve as a sustainable and cost-effective clayshale stabilization solution, contributing to improved stability and durability of infrastructure.